2016
DOI: 10.1002/bmc.3871
|View full text |Cite
|
Sign up to set email alerts
|

Geographical classification of Epimedium based on HPLC fingerprint analysis combined with multi‐ingredients quantitative analysis

Abstract: A reliable and comprehensive method for identifying the origin and assessing the quality of Epimedium has been developed. The method is based on analysis of HPLC fingerprints, combined with similarity analysis, hierarchical cluster analysis (HCA), principal component analysis (PCA) and multi-ingredient quantitative analysis. Nineteen batches of Epimedium, collected from different areas in the western regions of China, were used to establish the fingerprints and 18 peaks were selected for the analysis. Similari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…EBM is a traditional Chinese medicine, mainly used to treat various diseases such as sexual dysfunction and osteoporosis [17][18][19]. Furthermore, due to the protective effects of EBM on the reproductive system, immunity, cardiovascular, bone and nervous system, EBM has been added to various beverages in China.…”
Section: Discussionmentioning
confidence: 99%
“…EBM is a traditional Chinese medicine, mainly used to treat various diseases such as sexual dysfunction and osteoporosis [17][18][19]. Furthermore, due to the protective effects of EBM on the reproductive system, immunity, cardiovascular, bone and nervous system, EBM has been added to various beverages in China.…”
Section: Discussionmentioning
confidence: 99%
“…Some isolated studies indicated that the compounds of Epimedium from neighboring locations were similar (Huang et al, 2007;Xu et al, 2013;Xu et al, 2017). This study included samples from a wide geographical area and from different species (Table 1; Figure 1), as a way to offer a more comprehensive view of how location and species may affect biomass quality.…”
Section: Pca Analysismentioning
confidence: 99%
“…[10][11][12] Herba Epimedii contains various active ingredients [13][14][15] which dominantly include Epimedin C, Icariin > Epimedin B > Baohuoside I, Epimedin A. 16 However, the toxicity shows Epimedin C > Baohuoside I, Icariin, Epimedin A, Epimedin B as revealed by studies on laval and adult zebrafish. 17 Given the advantages of high content and hypotoxicity, Epimedin B might be a promising component to ameliorate osteoporosis.…”
Section: Introductionmentioning
confidence: 99%